2018
DOI: 10.1073/pnas.1808660115
|View full text |Cite
|
Sign up to set email alerts
|

Tunable stacking fault energies by tailoring local chemical order in CrCoNi medium-entropy alloys

Abstract: High-entropy alloys (HEAs) are an intriguing new class of metallic materials due to their unique mechanical behavior. Achieving a detailed understanding of structure-property relationships in these materials has been challenged by the compositional disorder that underlies their unique mechanical behavior. Accordingly, in this work, we employ first-principles calculations to investigate the nature of local chemical order and establish its relationship to the intrinsic and extrinsic stacking fault energy (SFE) i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
248
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 627 publications
(291 citation statements)
references
References 56 publications
39
248
2
2
Order By: Relevance
“…This was a surprising finding because the first-principle calculations predicted a stable hcp phase at low temperatures for a solid solution with a random distribution of constituent elements (19,35). One possible explanation is that, as a recent theoretical study suggested, the SFE varies widely depending on the short-range chemical order and can even become positive depending on the local configurations (36). Another possibility, as Ma et al (35) argued, is that the fcc phase may be stabilized by kinetics at low temperatures.…”
Section: Discussionmentioning
confidence: 97%
“…This was a surprising finding because the first-principle calculations predicted a stable hcp phase at low temperatures for a solid solution with a random distribution of constituent elements (19,35). One possible explanation is that, as a recent theoretical study suggested, the SFE varies widely depending on the short-range chemical order and can even become positive depending on the local configurations (36). Another possibility, as Ma et al (35) argued, is that the fcc phase may be stabilized by kinetics at low temperatures.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, the SQS method has been widely used to simulate the structures of metallic HEAs with a solid solution phase [25]. In addition, an SQS structure also serves as an initial structure followed by a combination of MC and DFT simulations to examine the occurrence of CSRO, which has been reported to occur in typical metallic HEAs such as Cr-Co-Ni [58,59] and affect mechanical properties such as stacking fault and point-defect energies. We focus on the SiGeSn HEA with the highest Sn content (i.e., where the ratio of the three elements is 1:1:1).…”
Section: Methodsmentioning
confidence: 99%
“…We then examine if the HEA exhibits a chemical short-range order (CSRO) which is a tendency for atomic clustering (e.g., one Si atom prefers Si/Ge neighbors over Sn atoms). CSRO has been reported in numerous HEAs and dominates several of their properties [58,59]. Furthermore, because point defects are unavoidable in any material due to thermal vibrations, we study the most basic point defect in the SiGeSn HEA, i.e., single vacancies.…”
Section: Ge Snmentioning
confidence: 99%
“…Such SRO arises from interactions between alloy elements, and has been experimentally observed or theoretically predicted for some multicomponent alloys [66][67][68][69][70]. In dilute alloys, the effect of SRO on strengthening has been historically envisioned through the formation of pairs, triplets or clusters, due to solute/solute interactions.…”
Section: Short Range Orderingmentioning
confidence: 99%